The Relationship between Dialysis Adequacy and Blood Pressure and Number of Intradialytic Hypotensive Episodes in Haemodialysis Patients - OĞUZ, SEMRA (My University, 2024)
Dialysis adequacy is currently defined as the dose of dialysis that covers all functions of the kidney and is measured by adequate removal of harmful substances and excess fluid accumulated in the body. The aim of this study is to examine the relationship between dialysis adequacy and blood pressure, as well as the number of intradialytic hypotensive episodes in hemodialysis patients. The study included 50 patients receiving four-hour hemodialysis three times a week at Muş State Hospital. Dialysis adequacy was based on Kt/V and URR values. Demographic data were collected by face-to-face interviews with the participants. Blood pressure, Kt/V, and URR were measured before the hemodialysis session, and then the total number of intradialytic hypotensive episodes within one hemodialysis session was recorded. There was no statistically significant correlation between Kt/V and systolic and diastolic blood pressure and number of intradialytic hypotensive episodes (P>0.05). There was no statistically significant correlation between URR and systolic and diastolic blood pressure and number of intradialytic hypotensive episodes (P>0.05). Our study shows that there is no significant relationship between dialysis adequacy and blood pressure and number of intradialytic hypotensive episodes. Further research is needed to understand how these relationships may vary among patient groups with different demographic and clinical characteristics. Keywords: Dialysis adequacy, Blood pressure, Intradialytic hypotension
Keywords: Dialysis adequacy; Blood pressure; Intradialytic hypotension